Testicular Structure and Spermatogenesis in the Naked Mole-Rat Is Unique (Degenerate) and Atypical Compared to Other Mammals - van der Horst, Gerhard; Kotzé, Sanet H.; O’Riain, M. Justin; Maree, Liana (Frontiers in Cell and Developmental Biology, 2019)
The naked mole-rat (NMR) queen controls reproduction in her eusocial colony by usually selecting one male for reproduction and suppressing gametogenesis in all other males and females. Simplified, polymorphic and slow-swimming spermatozoa in the NMR seem to have been shaped by a low risk of sperm competition. We hypothesize that this unique mammalian social organization has had a dramatic influence on testicular features and spermatogenesis in the NMR. The testicular structure as well as spermatogenic cell types and its organization in breeding, subordinate and disperser males were studied using light microscopy and transmission electron microscopy. Even though the basic testicular design in NMRs is similar to most Afrotheria as well as some rodents with intra-abdominal testes, the Sertoli and spermatogenic cells have many atypical mammalian features. Seminiferous tubules are distended and contain large volumes of fluid while interstitial tissue cover about 50% of the testicular surface area and is mainly composed of Leydig cells. The Sertoli cell cytoplasm contains an extensive network of membranes and a variety of fluid-containing vesicles. Furthermore, Sertoli cells form numerous phagosomes that often appear as extensive accumulations of myelin. Another unusual feature of mature NMR Sertoli cells is mitotic division. While the main types of spermatogonia and spermatocytes are clearly identifiable, these cells are poorly organized and many spermatids without typical intercellular bridges are present. Spermatid heads appear to be malformed with disorganized chromatin, nuclear fragmentation and an ill-defined acrosome formed from star-like Golgi bodies. Rudimentary manchette development corresponds with the occurrence of abnormal sperm morphology. We also hypothesize that NMR testicular organization and spermiation are modified to produce spermatozoa on demand in a short period of time and subsequently use a Sertoli cell “pump” to flush the spermatozoa into short tubuli recti and simplified rete testis. Despite the difficulty in finding cellular associations during spermatogenesis, six spermatogenic stages could be described in the NMR. These numerous atypical and often simplified features of the NMR further supports the notion of degenerative orthogenesis that was selected for due to the absence of sperm competition.